1979
DOI: 10.1210/jcem-49-5-770
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of a Basic Somatomedin: Comparison of Various Assay Techniques and Somatomedin Levels in Various Sera*

Abstract: Purification of a basic somatomedin (SM), with similarity to SM-C and insulin-like growth factor, from human plasma Cohn fraction IV-1 enabled development of a RIA based on this SM.SM antiserum was produced by immunizing rabbits with partially purified SM. This antiserum (final dilution, 1:50,000) specifically bound approximately 40% of added [125I]-SM in this RIA. The RIA sensitivity was 2 x 10(-4) U immunoreactive SM (IRSM). Highly purified SM-C, insulin-like growth factor 1, and our SM revealed parallel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 25 publications
(24 reference statements)
2
24
0
Order By: Relevance
“…My collaborator Sylvia van Buul-Offers found that bovine placenta contains both types receptors and developed an RRA allowing to measure both IGF-I and -II using the same tissue [236]. RIAs were developed for SM-C by Furlanetto et al [16]and Bala and Bhaumick [237]and others, and for SM-A by Hall et al [238]. These, of course, measured IGF-I.…”
Section: Sf As Endocrine Substancementioning
confidence: 99%
“…My collaborator Sylvia van Buul-Offers found that bovine placenta contains both types receptors and developed an RRA allowing to measure both IGF-I and -II using the same tissue [236]. RIAs were developed for SM-C by Furlanetto et al [16]and Bala and Bhaumick [237]and others, and for SM-A by Hall et al [238]. These, of course, measured IGF-I.…”
Section: Sf As Endocrine Substancementioning
confidence: 99%
“…The acidic-neutral group (pI less than 7.4) includes IGF-II (1), SM-A (4), and multiplication-stimulating activity (5). The basic group of somatomedins are highly similar in terms of their molecular weights, pls, NH2-terminal amino acid sequences (1-3), and immunoreactivity (3,6,7). IGF-I (similar to our basic SM) and IGF-II have different NH2-terminal amino acid sequences but share a sequence homology with each other and with proinsulin (8).…”
mentioning
confidence: 99%
“…Insulin was a gift from Eli Lilly. Peptides were iodinated by a modification of the chloramine-T method (6) to specific activities of 100-150 ,uCi of basic SM and 80-100 pCi of insulin per Ag (1 Ci = 3.7 x 1010 becquerels).…”
mentioning
confidence: 99%
“…The sensitivity of RIA for this antiserum was 10-25 pg/tube with 50% displacement at 125 pg/tube (0.25 ng/ ml). Thus, the sensitivity for IGF-I of this antiserum seem to be better than those reported previously (Bala & Bhaumick, 1979;Baxter et al, 1982;Furlanetto et al, 1977;Zapf et al, 1981). Using this RIA, we measured plasma IGF-I levels in various clinical conditions.…”
Section: Discussionmentioning
confidence: 46%